Feminist visual activism and the body - Sliwinska, Basia (New York, NY : Routledge, 2021)
"This book examines contemporary feminist visual activism(s) through the lens of embodiment(s). The contributors explore how the arts articulate and engage with the current sense of crisis and political concerns (e.g. equality, decolonization, social justice, democracy, precarity, vulnerability), negotiated with and through the body. Drawing upon the legacy of feminist art historical critique, the book scrutinizes activist strategies, practices, and resilience techniques in intersectional and transnational frameworks. It interrogates how the arts enable the creation of civil and political resilience, become engaged with politics as a response to disaster capitalism, and attempt to reform and improve society. The book will be of interest to scholars working in art history, visual culture, fine arts, women's studies, gender studies, feminism, and cultural studies"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Feminism and art; Art and social action